2021
DOI: 10.1177/00207640211045417
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning but not social capital is associated with better mental health in adolescents affected by violence and displacement by armed conflict in Colombia

Abstract: Background: The effect of the Colombian armed conflict on the mental health of adolescents is still poorly understood. Aims: Given social interventions are most likely to inform policy, we tested whether two potential intervention targets, family functioning and social capital, were associated with mental health in Colombian adolescents, and whether this was moderated by experience of violence and displacement. Methods: We examined the cross-sectional association between family functioning, cognitive social ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…(Yusuf Abdullah Aziz et al) (Tamayo-Aguledo et al, 2022;Kroplewski et al, 2019;Gonzálvez et al, 2019). However, some studies show that family functioning does not influence health outcomes but rather the influence of family support with autistic children (Khotibuddin & Shellia, 2022).…”
Section: Original Researchmentioning
confidence: 99%
“…(Yusuf Abdullah Aziz et al) (Tamayo-Aguledo et al, 2022;Kroplewski et al, 2019;Gonzálvez et al, 2019). However, some studies show that family functioning does not influence health outcomes but rather the influence of family support with autistic children (Khotibuddin & Shellia, 2022).…”
Section: Original Researchmentioning
confidence: 99%
“…There are other models focusing on ecological systems ( Bronfenbrenner, 1974 ; Sales and Irwin, 2013 ). Amongst different social contexts of adolescent development, the influence of the family in adolescent development has been highlighted (e.g., Hayek et al, 2022 ; Tamayo-Aguledo et al, 2022 ; Shek et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the McMaster family functioning model theory proposes six dimensions of family functioning, such as effective communication, clear family roles, and appropriate affective responses. Studies have revealed the positive impact of positive family functioning on the developmental outcomes of children and adolescents such as engagement in learning, happiness, mental health, and proper behaviors ( Izzo et al, 2022 ; Tamayo-Aguledo et al, 2022 ; Peng S. et al, 2023 ; Qi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%